UMP and Gaya Naturals Sdn. Bhd. to jointly develop patchouli oil project in Pahang - Hanafi, Anuwar (Penerbit UMP, 2015)
Universiti Malaysia Pahang (UMP) and Sabah-based company, Gaya Natural Sdn. Bhd., will be working together to establish the patchouli oil industry in Pahang.